2015
DOI: 10.5539/jps.v4n1p35
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Foliar NPK Fertilizer on Tea Yields in Kenya

Abstract: Economic evaluation analysis of foliar (NPK) fertilizer on tea yields was investigated on three varieties of tea grown in the Kenyan Highlands. Foliar fertilizers trial was setup on three sites, Meru, Kirinyaga and Kericho, comprising of 36 plots per site. Two foliar fertilizer types, Foliar Fertilizer 1 (FF1) and Foliar Fertilizer 2 (FF2), a positive control of Soil Fertilizer (SF) and a blank (FF0) were used to standardize the method. Yield analysis in Meru site showed significant increase (HSD=4.9, p≤0.05) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…ese findings are consistent with those by Njogu et al [16] that different clones have different nutritional needs and differ in their abilities to absorb nutrients even when the agronomic practices are similar, which is depicted in their yield response to varying fertilizer application rates and the fertilizer types applied. Different clones with different yield potentials require different fertilizer rates.…”
Section: Gross Profit Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…ese findings are consistent with those by Njogu et al [16] that different clones have different nutritional needs and differ in their abilities to absorb nutrients even when the agronomic practices are similar, which is depicted in their yield response to varying fertilizer application rates and the fertilizer types applied. Different clones with different yield potentials require different fertilizer rates.…”
Section: Gross Profit Analysissupporting
confidence: 92%
“…Fertilizer recommendations are based on field input trials and their effects on crop yield (yield responses) in both agronomic and economic terms [12][13][14][15]. Data from the crop responses to nutrients should always be subjected to economic analysis in order to account for differences in input and output and to identify the economic optimum rates (EORs) [16]. Several methods have been developed to internalize environmental issues in economic assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high electricity costs in the country and the high energy requirements in tea processing, sourcing power through the national grid has proven expensive. As such, to reduce the high-energy costs According to Njogu & Wachira (2015) the study identified a number of issues constraining growth along the value chain. The key issues identified at the production level, include: high labour cost, which account for to reduce the high cost at the production level and enhance productivity, there is need to promote mechanization and automating supply chain.…”
Section: Statement Of the Problemmentioning
confidence: 99%